Comparative perspectives : an introduction - Martin, Alexander J. (Pontificia Universidad Católica del Perú. Fondo Editorial, 2010)
In the last several decades there has been a marked rise in archaeological inquiries and a resulting rapid increase in the information available about past societies. As is common in scientific inquiry, this information has traditionally been organized through the lens of multiple scholarly paradigms (we can cite, among others, the processual movement, cognltlve and behavioral archaeologies, structural Marxism, post-processual approaches such as agent and landscape theory, etc). The discussion generated by the evaluation of these paradigms has been critica! in advancing our understanding of the human behaviors that produced the material record. However, as the acquisition of archaeological data becomes increasingly prolific, systematic, and standardized, it also becomes increasingly necessary to set clearer comparative frameworks that facilitate our understanding of multiple datasets gathered at multiple locations. As we enter the second decade of the new millennium, it is clear that the synthesis and comparison of data gathered by different researchers working throughout the world is one of the most useful avenues to refine our understandings of social processes. In this respect, South America stands as a valuable example of how a comparative perspective is increasingly important and how it can usefully be employed.

Durante las últimas décadas hemos experimentado un marcado incremento en las investigaciones arqueológicas y un consecuente rápido aumento en la información disponible acerca de las sociedades del pasado. Como es común en la mayoría de investigaciones científicas, esta información ha sido tradicionalmente organizada bajo el lente de varios paradigmas académicos. Podemos citar entre otros, el movimiento procesual, la arqueología cognitiva y del comportamiento, el Marxismo estructural, los enfoques posprocesuales como las teorías del paisaje y del agente, etc. La discusión generada por la evaluación de estos paradigmas ha sido crítica en el avance de nuestra comprensión acerca de los diversos comportamientos que produjeron el registro material. Sin embargo, ya que la adquisición de datos arqueológicos es cada vez más prolífica, sistemática y estandarizada, se vuelve cada vez más necesario fijar esquemas comparativos más claros que faciliten nuestra comprensión sobre las diversas bases de datos adquiridas en distintas localidades. Es así como, al entrar en la segunda década del nuevo milenio, es claro que la síntesis y comparación de los datos recopilados por los diversos investigadores que trabajan alrededor del mundo se presenta como una de las vías más útiles para perfeccionar nuestro entendimiento sobre los procesos sociales del pasado. Respecto a esto, América del Sur se presenta como un ejemplo valioso de cómo una perspectiva comparativa es cada vez más importante y de cómo esta puede ser usada provechosamente.
Perspectivas comparativas : una Introducción
Páginas 1-25
Keywords: Arqueología--América del Sur; https://purl.org/pe-repo/ocde/ford#6.01.02